Pengaruh light massage dan alternate nostril breathing exercise (ANBE) terhadap tekanan darah pada penderita hipertensi - Putri, Melsa; Husni, Husni; Wijaya, Andra Saferi; Heriyanto, Hendri; Nugroho, Nehru (Holistik Jurnal Kesehatan, 2026)
Background: Hypertension is a leading cause of degenerative diseases and death worldwide. Hypertension control efforts rely not only on pharmacological therapy but also on non-pharmacological interventions such as relaxation. Light massage and alternate nostril breathing exercises (ANBE) are complementary therapies known to help lower blood pressure. Purpose: To determine the effect of the combination of light massage and ANBE on changes in blood pressure in patients with hypertension. Method: This study used a quasi-experimental design with a pretest–posttest approach with a control group. The study was conducted from August to November 2025 in the Telaga Dewa Community Health Center area, Bengkulu City. A total of 42 participants were divided into two groups: an intervention group receiving light massage and ANBE, and a control group receiving slow deep breathing, each consisting of 21 participants. The interventions were administered twice daily for five days. The data were then analyzed using statistical tests according to the data distribution. Results: There was a significant difference between blood pressure before and after treatment in both groups (p = 0.001). The combination of light massage and ANBE was shown to significantly reduce systolic and diastolic blood pressure with a p-value of 0.012 (p ≤ 0.05). Conclusion: The combination of light massage and ANBE is effective in lowering blood pressure in patients with hypertension.   Keywords: Alternate Nostril Breathing Exercise (ANBE); Blood Pressure; Hypertension; Light Massage.   Pendahuluan: Hipertensi merupakan salah satu penyebab utama penyakit degeneratif dan kematian di seluruh dunia. Upaya pengendalian hipertensi tidak hanya mengandalkan terapi farmakologis, tetapi juga intervensi nonfarmakologis yang bersifat relaksasi. Light massage dan alternate nostril breathing exercise (ANBE) merupakan terapi komplementer yang diketahui dapat membantu menurunkan tekanan darah. Tujuan: Untuk mengetahui pengaruh kombinasi light massage dan ANBE terhadap perubahan tekanan darah pada penderita hipertensi. Metode: Penelitian desain quasi-experimental dengan pendekatan pretest–posttest with control group. Penelitian dilaksanakan pada bulan Agustus-November 2025, di wilayah kerja Puskesmas Telaga Dewa, Kota Bengkulu Sebanyak 42 partisipan dibagi menjadi dua kelompok, yaitu kelompok intervensi yang diberikan light massage dan ANBE, serta kelompok kontrol yang diberikan slow deep breathing, masing-masing terdiri dari 21 partisipan. Intervensi diberikan dua kali sehari selama lima hari. Selanjtunya data dianalisis menggunakan uji statistik sesuai dengan distribusi data. Hasil: Terdapat perbedaan yang signifikan antara tekanan darah sebelum dan sesudah perlakuan pada kedua kelompok (p = 0.001). Kombinasi light massage dan ANBE terbukti berpengaruh signifikan terhadap penurunan tekanan darah sistolik dan diastolik dengan nilai p = 0.012 (p ≤ 0.05). Simpulan: Kombinasi light massage dan ANBE efektif dalam menurunkan tekanan darah pada penderita hipertensi.   Kata Kunci: Alternate Nostril Breathing Exercise (ANBE); Hipertensi; Light Massage; Tekanan Darah.